Water Damage and Homeowner's Insurance: (2) C.L.U.E.® Report - Hyun-Jeong Lee; Kathleen C. Ruppert (EDIS)
FCS-3304, a 3-page fact sheet by Hyun-Jeong Lee and Kathleen C. Ruppert, tells homeowners Comprehensive Loss Underwriting Exchange (C.L.U.E.®) reports — what information is included, how they can be used by homebuyers and insurers, and your legal rights. Includes references and information on obtaining a free report. Published by the UF Department of Family Youth and Community Sciences, January 2009.